2020
DOI: 10.17921/1415-6938.2020v24n3p268-272
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae Grown in Cheese Whey and β-galactosidase Production

Abstract: O soro de queijo é o principal subproduto da indústria de laticínios e a alta demanda biológica e química de oxigênio (DBO e DQO) pode causar vários problemas ambientais. Estudos recentes apontam os potenciais usos biotecnológicos do soro de queijo, como o meio de fermentação, para a produção de β-galactosidase. A enzima é muito importante para hidrólise da lactose em galactose e glicose, monossacarídeos mais digeríveis pelo organismo humano. As microalgas podem produzir a β-galactosidase através de processos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Lactose degradation in microalgae is tightly connected with the strain's ability to produce β-galactosidase which enables lactose hydrolysis to glucose and galactose [14]. It was demonstrated that mixotrophy mode using cheese whey is the most efficient growth mode for Chlorella sp [15] [16]. However, there is a few works reporting the use of cheese whey for Chlorella vulgaris cultivation.…”
Section: Chlorella Vulgaris Growthmentioning
confidence: 99%
“…Lactose degradation in microalgae is tightly connected with the strain's ability to produce β-galactosidase which enables lactose hydrolysis to glucose and galactose [14]. It was demonstrated that mixotrophy mode using cheese whey is the most efficient growth mode for Chlorella sp [15] [16]. However, there is a few works reporting the use of cheese whey for Chlorella vulgaris cultivation.…”
Section: Chlorella Vulgaris Growthmentioning
confidence: 99%
“…Their ubiquitous presence spans various habitats, from lakes and oceans to wastewater facilities and even deserts 2 . They have gained signi cant attention for their potential applications in various elds, including bioremediation, biofuel production, environmental agents for wastewater treatment, cosmetics and food production 3,4 . Microalgae are cultivated as a source of highly valuable molecules, such as polyunsaturated fatty acid oils, pigments, and stable isotope biochemicals 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing agricultural production while preserving the environment has been a constant challenge for scientific research, as agricultural production systems need to meet the growing demand for food with the introduction of sustainable technologies (Mógor et al 2019;Chiaiese et al 2018) that demand natural inputs to the detriment of synthetics. In addition, the agroindustry generates large amounts of waste that can cause serious environmental problems if discarded incorrectly (Pereira et al 2021;Bosso et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, microalgal applications are gaining interest in agriculture since waste generated by the agroindustry showed great potential for microalgal mixotrophic cultivation (Pereira et al 2021). Several studies have been carried out to evaluate the efficiency of microalgal biomass production under different agro-industrial waste, such as cheese whey (Bosso et al 2020;Patel et al 2020) and desalination concentrate wastewater (Matos et al 2018). Microalgae are also expanding in agriculture due to the increased use of sustainable products such as biopesticides and biofertilizers that are being introduced into the market to replace agrochemicals, which are detrimental to the environment (Guo et al 2020).…”
Section: Introductionmentioning
confidence: 99%